Modelling the Effects of Forest use Change on Brownification of Finnish Rivers under Atmospheric Pressure - Katri Rankinen; Jose E. Cano Bernal; Maria Holmberg; Magnus Nordling; Torsti Schulz; Annikki Mäkelä; Ninni Mikkonen; Heini Kujala; Leah Jackson-Blake; Heleen A. de Wit; Martin Forsius (Environmental Management, 2025)
Browning of surface waters due to increased terrestrial loading of dissolved organic matter (DOM) is observed across the Northern Hemisphere. The effects influence several ecosystem services from freshwater productivity to water purification. Brownification is often explained by changes in large-scale anthropogenic pressures and ecosystem functioning (acidification, climate change, and land cover changes). This study examined the effect of forest use changes on water browning in Finland, considering the effects of global pressures. Our goal was to find the ecosystems and geographic areas that are most sensitive to environmental pressures that increase the loading of DOM. We were also looking for land use strategies that decrease browning. We combined mathematical watershed modelling to scenarios of climate change, atmospheric deposition, and forest use change. Changes included scenarios of forest harvest and protection on forest, that were derived from European Union’s regulation. The study area covered 20 watersheds from south to north of Finland. In northern Finland brownification continue. In southern Finland global influence (atmospheric deposition, climate change) seem to weaken, giving more space for local forest use change having an influence on brownification. Forest use change was more influential in river basins dominated by organic soils than in mineral soils. Extending forest protection decreased brownification especially in areas where the influence of atmospheric pressure is decreasing. When forest protection is planned to provide a carbon storage and sequestration potential and to favor biodiversity, it has favorable effect on surface water quality as well.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Quantification of the effect of environmental changes on the brownification of Lake Kukkia in southern Finland - Katri Rankinen; Virpi Junttila; Martyn Futter; José Enrique Cano Bernal; Daniel Butterfield; Maria Holmberg (Ambio, 2023)
The browning of surface waters due to the increased terrestrial loading of dissolved organic carbon is observed across the northern hemisphere. Brownification is often explained by changes in large-scale anthropogenic pressures (including acidification, and climate and land-use changes). We quantified the effect of environmental changes on the brownification of an important lake for birds, Kukkia in southern Finland. We studied the past trends of organic carbon loading from catchments based on observations taken since the 1990s. We created hindcasting scenarios for deposition, climate and land-use change in order to simulate their quantitative effect on brownification by using process-based models. Changes in forest cuttings were shown to be the primary reason for the brownification. According to the simulations, a decrease in deposition has resulted in a slightly lower leaching of total organic carbon (TOC). In addition, runoff and TOC leaching from terrestrial areas to the lake was smaller than it would have been without the observed increasing trend in temperature by 2 °C in 25 years.

Role of land cover in Finland’s greenhouse gas emissions - Maria Holmberg; Virpi Junttila; Torsti Schulz; Juha Grönroos; Ville-Veikko Paunu; Mikko Savolahti; Francesco Minunno; Paavo Ojanen; Anu Akujärvi; Niko Karvosenoja; Pirkko Kortelainen; Annikki Mäkelä; et al. (Ambio, 2023)
We present regionally aggregated emissions of greenhouse gases (GHG) from five land cover categories in Finland: artificial surfaces, arable land, forest, waterbodies, and wetlands. Carbon (C) sequestration to managed forests and unmanaged wetlands was also assessed. Models FRES and ALas were applied for emissions (CO 2 , CH 4 , N 2 O) from artificial surfaces and agriculture, and PREBAS for forest growth and C balance. Empirical emission coefficients were used to estimate emissions from drained forested peatland (CH 4 , N 2 O), cropland (CO 2 ), waterbodies (CH 4 , CO 2 ), peat production sites and undrained mires (CH 4 , CO 2 , N 2 O). We calculated gross emissions of 147.2 ± 6.8 TgCO 2 eq yr −1 for 18 administrative units covering mainland Finland, using data representative of the period 2017–2025. Emissions from energy production, industrial processes, road traffic and other sources in artificial surfaces amounted to 45.7 ± 2.0 TgCO 2 eq yr −1 . The loss of C in forest harvesting was the largest emission source in the LULUCF sector, in total 59.8 ± 3.3 TgCO 2 eq yr −1 . Emissions from domestic livestock production, field cultivation and organic soils added up to 12.2 ± 3.5 TgCO 2 eq yr −1 from arable land. Rivers and lakes (13.4 ± 1.9 TgCO 2 eq yr −1 ) as well as undrained mires and peat production sites (14.7 ± 1.8 TgCO 2 eq yr −1 ) increased the total GHG fluxes. The C sequestration from the atmosphere was 93.2 ± 13.7 TgCO 2 eq yr −1 . with the main sink in forest on mineral soil (79.9 ± 12.2 TgCO 2 eq yr −1 ). All sinks compensated 63% of total emissions and thus the net emissions were 53.9 ± 15.3 TgCO 2 eq yr −1 , or a net GHG flux per capita of 9.8 MgCO 2 eq yr −1 .

Modelling the regional potential for reaching carbon neutrality in Finland: Sustainable forestry, energy use and biodiversity protection - Martin Forsius; Maria Holmberg; Virpi Junttila; Heini Kujala; Torsti Schulz; Ville-Veikko Paunu; Mikko Savolahti; Francesco Minunno; Anu Akujärvi; Jaana Bäck; Juha Grönroos; Risto K. Heikkinen; et al. (Ambio, 2023)
The EU aims at reaching carbon neutrality by 2050 and Finland by 2035. We integrated results of three spatially distributed model systems (FRES, PREBAS, Zonation) to evaluate the potential to reach this goal at both national and regional scale in Finland, by simultaneously considering protection targets of the EU biodiversity (BD) strategy. Modelling of both anthropogenic emissions and forestry measures were carried out, and forested areas important for BD protection were identified based on spatial prioritization. We used scenarios until 2050 based on mitigation measures of the national climate and energy strategy, forestry policies and predicted climate change, and evaluated how implementation of these scenarios would affect greenhouse gas fluxes, carbon storages, and the possibility to reach the carbon neutrality target. Potential new forested areas for BD protection according to the EU 10% protection target provided a significant carbon storage (426–452 TgC) and sequestration potential (− 12 to − 17.5 TgCO 2 eq a −1 ) by 2050, indicating complementarity of emission mitigation and conservation measures. The results of the study can be utilized for integrating climate and BD policies, accounting of ecosystem services for climate regulation, and delimitation of areas for conservation.

Male predominance in disease severity and mortality in a low Covid-19 epidemic and low case-fatality area – a population-based registry study - Erik Forsblom; Suvi Silén; Elisa Kortela; Maarit Ahava; Hanna-Riikka Kreivi; Ville Holmberg; Asko Järvinen; Johanna Hästbacka; Sanna-Maria Kivivuori; Atte Meretoja (Infectious Diseases, 2021)

Forest floor vegetation response to nitrogen deposition in Europe - Thomas Dirnböck; Ulf Grandin; Markus Bernhardt‐Römermann; Burkhardt Beudert; Roberto Canullo; Martin Forsius; Maria‐Theresia Grabner; Maria Holmberg; Sirpa Kleemola; Lars Lundin; Michael Mirtl; Markus Neumann; et al. (Global Change Biology, 2014)
Chronic nitrogen (N) deposition is a threat to biodiversity that results from the eutrophication of ecosystems. We studied long‐term monitoring data from 28 forest sites with a total of 1,335 permanent forest floor vegetation plots from northern Fennoscandia to southern Italy to analyse temporal trends in vascular plant species cover and diversity. We found that the cover of plant species which prefer nutrient‐poor soils (oligotrophic species) decreased the more the measured N deposition exceeded the empirical critical load ( CL ) for eutrophication effects ( P = 0.002). Although species preferring nutrient‐rich sites (eutrophic species) did not experience a significantly increase in cover ( P = 0.440), in comparison to oligotrophic species they had a marginally higher proportion among new occurring species ( P = 0.091). The observed gradual replacement of oligotrophic species by eutrophic species as a response to N deposition seems to be a general pattern, as it was consistent on the European scale. Contrary to species cover changes, neither the decrease in species richness nor of homogeneity correlated with nitrogen CL exceedance (ExCL emp N). We assume that the lack of diversity changes resulted from the restricted time period of our observations. Although existing habitat‐specific empirical CL still hold some uncertainty, we exemplify that they are useful indicators for the sensitivity of forest floor vegetation to N deposition.

Neuromuscular and circulatory adaptation during combined arm and leg exercise with different maximal work loads - Thibault Brink-Elfegoun; Hans-Christer Holmberg; Maria Nordlund Ekblom; Björn Ekblom (European Journal of Applied Physiology, 2007)

Long-Term Base Cation Balances of Forest Mineral Soils in Finland - Päivi Joki-Heiskala; Matti Johansson; Maria Holmberg; Tuija Mattsson; Martin Forsius; Pirkko Kortelainen; Lena Hallin (Water, Air, & Soil Pollution, 2003)